THE REVITALIZATION OF THE INDONESIAN LEGAL SYSTEM IN THE ORDER OF REALIZING THE IDEAL STATE LAW - Fauzia, Ana; Hamdani, Fathul; Octavia, Deva (Faculty of Law-Universitas Bandar Lampung, 2021)
It can be called that the dynamics of national and state life in Indonesia are increasingly being tested by the same problem. For example, an outbreak of judicial corruption from the time to time, which was never ending. Law enforcers who are echoed as honorable professions, but on the other hand, these are exacerbated by the corrupt behavior of those professions. The sale and purchase of a case is no longer viewed as taboo, indeed it just looks like proper. Which means, it is a kind of a sign that the various legal regulations that normatively regulate the entire judicial process are ultimately unable to overcome the judicial corruption. The main objective of this research focuses on analysis related to efforts to revitalize the legal system in order to create an ideal rule of law as stated by Lawrance Friedman in his book namely